One‐Pot Two‐Step Synthesis of 1‐(Ethoxycarbonyl)indolizines via Pyridinium Ylides. Issue 28 (12th August 2013) - Allgäuer, Dominik S.; Mayr, Herbert
Abstract: Pyridinium salts Py + ‐CH2 ‐EWG (EWG = CO2 Et, CONEt2, CN, COMe, COPh) reacted with Michael acceptors Ar‐CH=C(CO2 Et)(Acc) (Acc = CO2 Et, COMe, SO2 Me, CONH2 ) at ambient temperature in the presence of base to give [3 + 2]‐cycloadducts by stepwise [3 + 2]‐cycloaddition of the intermediate pyridinium ylides. Treatment of the crude reaction mixtures with 1 equiv. of chloranil and atmospheric oxygen in the presence of sodium hydroxide gave 1‐(ethoxycarbonyl)indolizines by dehydrogenation and elimination of the acceptor group (Acc). A good yield of indolizine was also obtained from Py + ‐CH2 CN and i Pr‐CH=C(CO2 Et)2, which indicates that this method is not restricted to aromatic Michael acceptors. Structurally related isoquinolinium salts react with Michael acceptors analogously to give pyrrolo[2, 1‐ a ]isoquinolines. Abstract : Pyridinium salts reacted with Michael acceptors in the presence of base to generate [3 + 2]‐cycloadducts at ambient temperature. Hydroxide‐induced oxidation of the crude [3 + 2]‐cycloadducts with chloranil (1 equiv.) and atmospheric oxygen yielded 1‐ethoxycarbonyl‐substituted indolizines.